Dietary Fermentable Fibers Attenuate Chronic Kidney Disease in Mice by Protecting the Intestinal Barrier. Issue 4 (11th April 2018) - Hung, Tran Van; Suzuki, Takuya
Abstract: Background: Chronic kidney disease (CKD) is a worldwide health problem. Although the pathogenesis of CKD is still unclear, recent studies suggest that systemic inflammation caused by a dysregulated microflora and an impaired intestinal barrier is involved in CKD development. Objective: We investigated the effects of the fermentable dietary fibers (DFs), unmodified guar gum (GG), and partially hydrolyzed GG (PHGG) (i.e., substances with distinct viscosity characteristics) on CKD development, with a particular focus on colonic tight junction (TJ) barriers in mice. Methods: Male 7-wk-old ICR mice were fed an AIN-93G diet that contained 0.25% adenine for 2 wk to induce CKD. Mice fed adenine were then divided into 3 groups and fed the unsupplemented diet (CKD) or a diet containing 10% PHGG (CKD+PHGG) or GG (CKD+GG) for 3 wk. Control (CON) mice were fed an AIN-93G diet without adenine throughout the 5-wk experiment. Plasma urea concentration; the colonic TJ proteins zonula occludens (ZO) 1, ZO2, occludin, junctional adhesion molecule A (JAMA), and claudin isoforms; renal inflammatory cytokines tumor necrosis factor α ( Tnfa ), interleukin ( Il  ) 1β ( Il1b), and Il6 ; and cecal short-chain fatty acids (SCFAs) and microflora were analyzed. Results: Compared with the CON, CKD+PHGG, and CKD+GG groups, the CKD group had a 2.2- to 4.4-fold higher plasma urea concentration and greater expression of inflammatory cytokine genes in the kidney, including Tnfa (4.4- to 48-fold), Il1b (4.6- to 56-fold), and Il6 (8.8- to 115-fold). The CON, CKD+PHGG, and CKD+GG groups had greater expression of colonic TJ proteins including ZO1 (2.9- to 3.7-fold), ZO2 (3.4- to 4.3-fold), occludin (3.0- to 3.3-fold), JAMA (4.4- to 5.4-fold), and claudin 7 (2.1- to 2.6-fold) and higher cecal SCFA (1.8- to 3.5-fold) and Lactobacillus (2.7- to 4.0-fold) concentrations than the CKD group. Conclusion: Supplemental feeding with fermentable DFs, such as GG and PHGG, might be effective for the prevention or management of CKD by restoring colonic barrier integrity and microflora composition, as shown in mice.